Designing an IoT-based footstep counter for sports shoes - Aditya, Vikra; Ilham, Dirja Nur; Atabiq, Fauzun; Jannah, Dina Miftahul; Harahap, Muhammad Khoiruddin (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2023)
Shoes are general footwear that can be used when exercising, working, formal events, or just to sweeten your appearance. Shoes used for sports have a slightly different shape from shoes in general, in terms of covering the left and right sides, the base, and the design, but most shoes do not have a device to count the steps taken. To overcome this, researchers have created a tool in shoes that can count the user's footsteps while exercising. A step counter on shoes based on the internet of things uses NodeMCU and an IR sensor which functions to detect every step of the shoe wearer. The result of the detected step count will be displayed in the blynk application. NodeMCU and IR sensors will be connected to the Blynk application using the internet network. When the step counter on the shoe and the hotspot are turned on, the results of the foot count will appear on the Blynk application on the smartphone. Footstep data detected by the IR sensor corresponds to the number of steps counted manually. The test results from a 150-meter step counter, obtained results of 207 steps in 3 minutes when walking casually, 223 steps in 1 minute 30 seconds when walking fast, and 264 steps when running in a period of 1 minute 15 seconds.